Measurement of Poverty, Undernutrition and Child Mortality - Misselhorn, Mark (Goettinger Studien zur Entwicklungsoekonomik / Goettingen Studies in Development Economics, 2018)
Although the world has seen a strong increase in global incomes in the last two decades and consequently a decline in global poverty rates, the number of persons living in absolute poverty remains on unacceptably high levels. Besides rising incomes can not distract from the fact that resources to fight global problems remain scarce. These resources have to be devoted to the fight against different global problems like the fight against communicable and non-communicable diseases (especially HIV/AIDS and Malaria) or the fight against global warming. The main precondition to achieve the best results with these limited resources is a good knowledge about the determinants and the best policies to fight each problem. But before being able to analyze the determinants of the different global problems and especially of poverty, it is of fundamental importance to find the right indicators for each phenomenon. This book contributes to the discussion of appropriate poverty indicators for the different dimensions of poverty like income poverty, undernutrition and child mortality and proposes a multidimensional poverty indicator that takes the income distribution into consideration.